Access : introduction to travel and tourism - Mancini, Marc (Delmar Cengage Learning, 2012)
With updated coverage of technology, new profiles of industry leaders additional activities, refined graphics and full-color photos, this concise book provides readers with a wealth of practical information designed to help them refine their research skills, respond to real-world scenarios, identify key concepts, and remember critical information